Footprints in the sand (big book) (Nelson Australia South Melbourne, 1994)
"Footprints in the Sand" is a poignant story that explores themes of faith, love, and support during life's challenges. The narrative centers around a person who dreams they are walking along a beach with the Lord, where scenes from their life are reflected in the sand. During difficult times, they notice that only one set of footprints appears, leading them to question why they were left alone. The comforting response reveals that during those times, the Lord carried them. This touching tale emphasizes the idea of divine presence and guidance in moments of struggle, offering reassurance and hope to readers. Its powerful message resonates with many, making it a cherished piece of inspirational literature.